Factors associated with overall and high-risk return visits to the emergency department: a vital sign trajectory approach - Hsiao-Chia Wang; Cheng-Chung Fang; Chien-Hua Huang; Jun-Wan Gao; Jiann-Hwa Chen; Chu-Lin Tsai (BMC Emergency Medicine)
Abstract Background For patients and emergency department (ED) physicians, return visits to the ED represent a potentially detrimental issue. In this study, our goal was to examine factors associated with overall and high-risk ED revisits. Specifically, as vital signs during the ED stay may provide important clues for subsequent revisits, we also examined the association between vital sign trajectories and post-ED revisits. Methods This retrospective cohort study utilized electronic clinical warehouse data from a tertiary medical center. We retrieved data from 454,330 ED visits over four years. The data included patient demographics, triage data, and repeated vital sign measurements. Group-based trajectory modeling was used to identify vital sign trajectories. A high-risk return ED visit was defined as a revisit within 72 h of the index visit with intensive care unit admission, receiving emergency surgery, or with in-hospital cardiac arrest. Multivariable logistic regression analysis was performed to evaluate the associations between vital sign trajectories and revisits. Results A total of 39,138 potential index ED visits were analyzed. Of these, 3,201 resulted in revisits, accounting for an 8.2% overall revisit rate and a 0.2% high-risk revisit rate. A high but resolving body temperature trajectory was associated with overall revisits (adjusted odds ratio [aOR], 1.32; 95% confidence interval [95% CI], 1.13–1.53). By contrast, high-risk revisits were associated with a low/fluctuating oxygen saturation trajectory (aOR, 2.40; 95% CI, 1.15–4.99). Older age (aOR, 1.27 per 10-year increase; 95% CI, 1.11–1.46) and having a chronic major disease (aOR, 2.30; 95% CI, 1.38–3.84) were also associated with high-risk revisits. Conclusions In addition to older age and having a chronic major disease, a low and fluctuating oxygen saturation trajectory during the index ED stay may signal subsequent high-risk revisits. Thus, discharge decisions should be carefully re-evaluated in these high-risk populations.